Feature Extraction Trends for Intelligent Facial Expression Recognition: A Survey - Azam, Irfan; Ali Khan, Sajid (Informatica, 2018)
Human facial expression is important means of non-verbal communication and conveys a lot more information visually than vocally. In Human-machine interaction facial expression recognition plays a vital role. Still facial expression recognition through machines like computer is a difficult task. Face detection, feature extraction and expression classification are the three main stages in the process of Facial Expression Recognition (FER). This survey mainly covers the recent work on FER techniques. It especially focuses on the performance including efficiency and accuracy in face detection, feature extraction and classification methods.